Nigeria and conflict resolution in Africa: The Darfur experience (2011)
Conflicts in Africa have over the years led to loss of lives; displacement of persons and misery in many parts of the continent. The need to resolve; manage and prevent these conflicts; and equally deal with the socio-economic challenges arising from these conflicts has become a source of worry to African nations including Nigeria; the giant of Africa. It is in the light of the foregoing therefore; that this paper attempts to analyze Nigeria s role in conflict resolution in Africa using the Darfur crisis in Sudan as a case study. The paper examines the historical background of the Darfur conflict and efforts made by Nigeria to resolve the crisis through peace initiatives. Since the restoration of peace in Darfur is a big challenge facing the African continent; the paper looks at the problems and prospects of peace in that part of the continent. The paper concludes by positing that even though Nigeria has demonstrated its commitment in resolving the conflict in Darfur; there still is a lot to do in concert with the African Union; especially now that Southern Sudan is a sovereign state.